Analisis Semantik pada Lirik Lagu Cinto Indak Sapadan oleh Rayola - Nabilla Syaren (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
An idea, idea or thought of a person is all conveyed through ahasa because language is a bridge for the delivery of these ideas or thoughts, with that everything that wants to be expressed can be conveyed well, of course, with the use of good and correct language (Brastyan, Andini Prima 2019:14). In this study, the author uses a qualitative approach in terms of the study of semiotics, therefore why in this study we focus on the analysis of semiotics in a song entitled cinto indak sapadan sung by Yola Aurelia Laksmi or widely known as Rayola (2024). The song cinto indak sapadan is a song written by Rozac Tanjuang and popularized by Rayola which was launched on 2024-02-01, this song uses the Minang language which is full of meaning. In the analysis of this song, it teaches us about the meaning of sincerity and must accept something that does not suit us and better understand the meaning of the song when we understand the science in semantics as a means of understanding the lyrics of the song that we analyze.